Food Safety Interventions to Control Listeria monocytogenes in the Fresh Apple Packing Industry: A Review. Issue 6 (3rd October 2019) - Pietrysiak, Ewa; Smith, Stephanie; Ganjyal, Girish M
Abstract: Listeria monocytogenes, in fresh and ready‐to‐eat produce such as whole fresh apples, is of concern as there is no "kill step" in their packing process that would eliminate the pathogenic bacteria. Recent listeriosis outbreaks revealed that insufficient cleaning and sanitation practices in fresh apple packing houses may lead to contamination of fruit with L. monocytogenes . This article discusses three fundamental aspects for ensuring microbiological safety of fresh apples: protection of fresh apples from microbial contamination during the packing process, decontamination intervention techniques, and the challenges in removal of L. monocytogenes from fresh apples. Currently used and novel methods of fresh produce decontamination are discussed and evaluated on their usefulness for the apple packing process. Additionally, present regulatory requirements, possible routes of produce contamination, and bacteria attachment and survival mechanisms are described. Optimum methods for microbial decontamination of whole fresh apples are still to be determined. Critical aspects that should be considered in developing the interventions include apple morphology, conditions and scale of the packing process, and influence of the interventions on apple quality. Evaluation of the currently used and emerging decontamination methods indicated that the hurdle technology and rotating use of sanitizers to avoid development of bacterial biofilm resistance may give the best results, although not conclusively.